THE CORRELATION BETWEEN VISCERAL FAT LEVELS AND LIPID PROFILE IN OBESE ADULTS - Sumarni, Sumarni (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
This study aims to find out the correlation between visceral fat levels and lipid profile in obese adults. The research was conducted by using the cross-sectional design with 67 samples, including 34 obese adults and 33 nonobese adults aged 25-50 years old. The visceral fat levels were measured by using Body Impedance Analysis; while the lipid profile was examined through a standardized test. The results reveal that in terms of visceral fat parameter, there is a significant difference between obese adults and non-obese adults groups (p<0.000); while in terms of lipid profile, there is no any significant difference (p>0.05). The bivariate correlation analysis shows that there is a significant positive correlation between visceral fat levels and total cholesterol (r = 0.392; p = 0.001), LDL cholesterol (r = 0.286; p = 0.019), triglycerides (r = 0.475; p = 0.000) and the ratio of TG / HDL (r = 0.463; p = 0.000). The linear regression multivariate analysis shows that only total cholesterol and triglyceride have big contribution to the change of visceral fat levels (27.2%). Keywords: visceral fat level, lipid profile, obese adults Penelitian ini bertujuan untuk mengetahui korelasi antara derajat lemak viseral dengan profil lipid pada dewasa obes. Desain penelitian adalah cross-sectional dengan sampel 67 orang, terdiri dari 34 dewasa obes dan 33 dewasa nonobes, berumur 25-50 tahun. Derajat lemak viseral diukur dengan Body Impedance Analysis dan profil lipid diperiksa dengan pengukuran yang terstandarisasi.Hasil penelitian menunjukkan bahwa terdapat perbedaan derajat lemak viseral yang bermakna pada kelompok dewasa obes dan nonobes (p=0,001). Adapun pada profil lipid tidak berbeda bermakna antara dua kelompok (p>0,05). Analisis korelasi bivariat menunjukkan adanya korelasi positif yang bermakna antara derajat lemak viseral dengan kolesterol total (r = 0,392 ; p = 0,001), kolesterol LDL (r = 0,286 ; p = 0,019), trigliserida (r =0,475 ; p = 0,000) dan rasio TG/HDL (r = 0,463 ; p = 0,000). Sedangkan antara derajat lemak viseral dengan kolestrol LDL tidak terdapat korelasi yang bermakna. Analisis multivariat regresi linear menunjukkan bahwa hanya kolesterol total dan trigliserida yang berkonstribusi besar pada perubahan derajat lemak viseral sebesar 27,2%. Kata kunci : derajat lemak viseral, profil lipid, dewasa obes